Analisis Perilaku Karakter Marisol Dalam Film A Man Called Otto Sebagai Representasi Kepedulian Sosial - Ridi Nismoro; Henny Sri Mulyani; Lilis Puspitasari (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
This study aims to analyze the character of Marisol in the film "A Man Called Otto" as a representation of the attitude of social care. Marisol is portrayed as a social activist who cares about the welfare of the surrounding community. The method used in this research is Roland Barthes semiotic analysis with a qualitative descriptive approach. The data collection techniques used are observation techniques, documentation techniques, and literature study techniques. The data is analyzed to identify how Marisol's social care attitude is reflected in her social interactions, real actions, as well as her thoughts and motivations. The results show that in the 8 scenes analyzed on Marisol's character, it shows that Marisol's character plays an important role in exploring the complexity of social care attitudes. Through her actions and sincere attitude towards social issues, Marisol represents the struggle for social justice and concern for human rights. The analysis also highlights how the character stimulates reflection in the audience on the importance of social care in shaping a more just and inclusive society.